Implementasi Data Mining Klasifikasi Algoritma C4.5 Dalam Perekrutan Perangkat Desa - Puspa, Misrawati Aprilyana (Forum Kerjasama Pendidikan Tinggi, 2019)
This study aims to The office of the Head held a village apparatus recruitment process that was still done manually. The obstacle found in the process of accepting village officials is the number of applicants received is limited. The purpose of this rsearch is to help facilitate the office of the village The method used is the C4.5 algorithm is one method that can analyze large amounts of data or commonly called data mining. In this study an application was made that implements a decision tree with the C4.5 algoritthm , the results of this study are in the form of an application program based on the conditions of the decision tree results that have been found to determine the recruitment of village officials